Clinical relevance of hyperamylasemia and pancreatitis-like imaging linked with accidental hypothermia - Erika Yawata; Yuuki Bamba; Yosuke Kawai; Hiroyuki Honda; Kei Nishiyama (PLoS ONE, 2026)
Background Elevated pancreatic enzymes and pancreatitis-like imaging findings have been reported in patients with accidental hypothermia; however, their clinical significance remains unclear. This study aimed to explore a serum amylase threshold that may support consideration of computed tomography (CT) for evaluating pancreatitis-like findings in accidental hypothermia and describe the clinical course of affected patients. Methods We conducted a retrospective single-center observational study of adult patients with accidental hypothermia admitted to a tertiary emergency and critical care center in Japan between November 2011 and April 2023. Accidental hypothermia was defined as a core body temperature <35°C. Receiver operating characteristic (ROC) analysis was performed to evaluate the ability of serum amylase levels to identify pancreatitis-like CT findings. Patients with hyperamylasemia and pancreatitis-like CT findings were descriptively analyzed. Results Among 169 patients included in the study, 36 (21.3%) had hyperamylasemia. Pancreatitis-like CT findings were observed in 14 patients, of whom 13 had hyperamylasemia. ROC analysis among patients who underwent CT evaluation identified 428 IU/L as a serum amylase threshold associated with pancreatitis-like CT findings (area under the curve, 0.91; sensitivity, 93%; specificity, 86%). The positive and negative predictive values were 44.8% and 99.0%, respectively. Most CT abnormalities consisted of localized peripancreatic fat stranding, fluid collection, or pancreatic enlargement. No patients developed pancreatic necrosis or required invasive pancreatic intervention. Most patients were managed conservatively with fluids and nutritional support, and short-term outcomes were generally favorable. Conclusions In patients with accidental hypothermia, serum amylase levels ≥428 IU/L may support consideration of CT evaluation of pancreatitis-like findings. Although hyperamylasemia alone showed limited positive predictive value, most patients with pancreatitis-like CT findings had favorable short-term outcomes with conservative management.